Comparison between Indian spinach production in aquaponics utilizing fish wastewater and hydroponics biogas slurry solution - Bably Akter; Farjana Akhter; Shaharior Hashem; Md. Hamidur Rahman; Homayora Yeasmin; S. M. Rayhan (Journal of Fisheries, 2025)
The experiment compared Indian spinach production in aquaponics utilizing fish wastewater and hydroponics with biogas slurry solution. The aquaponics system involved 60 juvenile tilapias, released into a 750 L tank with an average initial length and weight of 14.41 ± 0.66 cm and 49.81 ± 4.29 g, respectively. The fish were fed commercial pelleted feed twice daily and maintained suitable water quality parameters, including pH, temperature, and DO, within the required range. The hydroponics system used biogas slurry as nutrient media. In each system, 3 plant beds were used, and 4 Indian spinach plants were planted in each bed. Physical parameters of water indicated that the aquaponics system had higher levels of EC, HCO3, CO3, Total-N, potassium, sulphur, and sodium than the hydroponics system. After 90 days, aquaponics had the largest plant weight (82.05 ± 23.31 g), with significantly higher levels of nitrogen, potassium, and sulphur content (by 5.54%, 3.10%, and 0.61% respectively) in leaves was found in aquaponics, while the phosphorus (0.85%) was higher in hydroponics. The yield of Indian spinach was higher in aquaponics (2.88 kg m–2) than in hydroponics (1.52 kg m–2). Length gain of experimental fish in aquaponics was 10.54 ± 1.51 cm, weight gain 112.71 ± 21.75 g, with a percent weight gain of 227.23 ± 42.98, specific growth rate of 1.4 ± 0.16% day–1, which was normal. The study concluded that wastes from tilapia aquaponics are more suitable for Indian spinach cultivation than low-cost biogas slurry hydroponics.